Calculation of the diploid chromosome number for the taxa of the genus Vicia L. (Fabaceae) in Iraqi Kurdstan District - Athiya N. Al-Mashhadani; Shwan M. Salih (Journal of Madenat Alelem University College, 2015)
The current study was included the calculation of the diploid chromosome number for the taxa of the genus Vicia L. growing in Iraqi Kurdistan districts which are of 27 taxa. The chromosomes were calculated from the somatic cells of the anther cover, the best phase for this study was the metaphase of mitosis. The basic chromosome number for that taxa were found to be 5, 6 and 7.The taxa of the genus Vicia under the study have a clear variations in their chromosomes number and size. So the diploid number are 2n=10, 2n=12, 2n=14, 2n=24, and 2n=28, the last two numbers were a tetraploidy for the basic numbers 6 and 7, respectively. The diploid chromosome numbers for most of the Vicia species are recorded in Iraq for the first time as known from the available references.